Kewirausahaan Sosial Pada Pondok Pesantren Sidogiri Pasuruan - Reginald, Azel Raoul; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Joblessness and lack of social welfare are economic problems which require the involvement of all people to overcome. The education aspect which functions to prepare educated human resource also plays important roles in reducing the level of joblessness and increase the social welfare. Islamic Boarding School Sidogiri Pasuruan as an educational institution not only provides Salaf education materials, but gives social benefits through its social entrepreneurship program.The aim of this research is to discover the social entrepreneurship applied at Islamic Boarding School Sidogiri Pasuruan. This research uses qualitative descriptive approach, by using a qualitative research of case study. Technique of data collection applied in this research is through documents, interview, participatory observation, and documentation upon the informants selected by using purposive sampling methods.The results of the research show that the application of social entrepreneurship at Islamic Boarding School Sidogiri Pasuruan can be proven by the innovation of establishment of social entrepreneurship institution, i.e. Kopontren Sidogiri (Cooperative of Islamic Boarding School Sidogiri), Pustaka Sidogiri, Buletin Sidogiri (Sidogiri Buletin), BMT Maslahah, BMT UGT Sidogiri, BPRS UMMU Sidogiri dan Koperasi Agro Sidogiri (Sidogiri Agribusiness Cooperative). They have been established based on the ideas and roles of civil society of Islamic Boarding School Sidogiri Pasuruan to maintain the economic activities, i.e. the duty of delivering Islamic values (dakwah), business, and providing social values for the society around Islamic Boarding School Sidogiri Pasuruan.